Semantic Changes of English Loanwords in Radar Kediri Daily Newspaper Headlines - Moh Khoirul Anam; Deli Nirmala (PAROLE: Journal of Linguistics and Education, 2019)
Use of English loanwords in mass media like newspapers is so prominent. However, the writers still use the words even though the words go through meaning changes. Hence, this study aims to investigate why the writers still use loanwords in their article. Loanwords from the headline of Radar Kediri were taken as data. There were sixty-seven English loanwords variations used in the articles of the headlines in the time span of the study. Close and open questionnaires were administered to the writers and the editors of the headline articles. Questionnaires encompassed the English loanwords which the writers wrote in their articles were administered to them. Interviewing the other editor was also used as data crosschecks. This study found that, first, there are six different categories undergoing a meaning change in the headline of Radar Kediri based on Bloomfield semantic change classification, viz, Narrowing, Widening, Metaphor, Synecdoche, Degeneration, and Elevation. Second, there are six reasons why the writers use English loanwords in their articles: be more effective in conveying a message, be more global/common in use, be more modern, be more educated, to vary vocabulary in a sentence by using synonymous, and to avoid monotony